Trade policy within the context of the World Trade Organization - Tussie, Diana (1997)
Looks at the main obligations arising from the World Trade Organization and their repercussions on the design of trade policy. Analyses the context of the world trade system and the problems it raises, and highlights the fact that, as the number of questions considered expands and a ever-increasing number of policies are brought under international scrutiny, the delicate balance between trade policy and negotiations must be adjusted more and more exactly.